Disturbance factors identified in the environmental protection area corumbataí-Botucatu-tejupá, Botucatu-perimeter, State of São Paulo - Pollo, Ronaldo Alberto [UNESP]; De Oliveira Ferreira Silva, César [UNESP]; Cardoso, Lincoln Gehring [UNESP]; Lessa, Luís Gustavo Frediani [UNESP] (My University, 2019)
The satellite images with high spatial resolution have become very important in the action of analysis, interpretation and quantification of the environmental transformations that have occurred over time, looking for the monitoring of land use and land cover dynamics on protected areas by law, thus facilitating the search for sustainable development and making it possible to reconcile agricultural production by the natural resources protection. The present work is a spatial analysis of the perturbation factors and their potential environmental impacts on the water resources identified in the Environmental Protection Area (EPA) – Botucatu-SP Perimeter this portion located within the municipality of São Manuel, State of São Paulo, through digital images of Google Earth Pro since the years of 2010 to 2016. It was identified eight areas with perturbation factors (A, B, C, D, E, F, G, H), where it was possible to detect points of deforestation and the pasture and monoculture crops increase in areas of environmental preservation, such as springs and places of potential aquifer recharge. These irregular occupations generate impacts on water production, such as soil sealing, runoff and erosion with sediment transport. This procedure is applicable to municipalities of small and medium size to detect and monitor environmental nonconformities.
Fatores de perturbaÇÃo identificados em Área de proteÇÃo ambiental corumbataÍ-Botucatu-tejupÁ, perÍmetro Botucatu, Estado de SÃo Paulo
Keywords: Environmental impacts; Geoprocessing; Google earth